A Motivasi Intrinsik Dan Ekstrinsik Mengikuti Pembelajaran PJOK: Sistematic Literatur Review - Kadek Dedy Teriana; I Wayan Artanayasa; Luh Putu Tuti Ariani; Kadek Yogi Parta Lesman; I Ketut Iwan Swadesi (Jurnal Porkes, 2026)
Low academic achievement in Physical Education is often attributed to students’ lack of motivation, whether intrinsic or extrinsic. This study aims to analyze and synthesize scientific evidence regarding the influence of these two types of motivation on PE learning outcomes through a systematic literature review. Articles were searched for in leading scientific databases using relevant keywords, with the selection process following the PRISMA 2020 guidelines and the SALSA framework. A total of eight articles met the inclusion criteria based on the PICOS framework. The synthesis results indicate that intrinsic motivation, which originates from within the students themselves, has a dominant influence in fostering active engagement, perseverance, and sustained learning success. Meanwhile, extrinsic motivation, such as teacher support, rewards, and a conducive learning environment, plays a crucial role as an initial trigger for student engagement. A synergistic combination of intrinsic and extrinsic motivation has been shown to contribute most effectively to improved learning outcomes in cognitive, affective, and psychomotor aspects. The magnitude of motivation’s contribution to learning outcomes varies between 8.2% and 52.4% across studies. Therefore, physical education teachers are advised to design learning strategies that comprehensively foster intrinsic motivation while strengthening extrinsic support to achieve optimal learning outcomes.